78PLy6G+ cells in irradiated tumour tissue promote glioblastoma cell dedifferentiation and tumour recurrence. (7th November 2019) - Seo, S; Jeon, H-Y; Kim, H
Abstract: Background: Most of glioblastomas (GBMs) frequently recur at sites of radiotherapy, but it is unclear if changes in the tumor microenvironment by radiotherapy affect GBM recurrence. Methods: GBM cells were injected into the nude mice brain. At 3 weeks post injection, the whole brains of mice were irradiated 5 times at 2 Gy per day. Rat anti-Ly6G antibodies were used for Ly6G+ inflammatory cell depletion to figure out the roles of Ly6G+ cells in irradiated tumor tissue. To detect cell senescence, non-irradiated or irradiated GBM cells and xenograft tumor sections were stained by using a Senescence β-Galactosidase Staining Kit. Bioinformatics analysis, tubule formation and cell invasion assays were used to unveil GBM cell dedifferentiation and changes in cellular properties. Results: Radiation-induced senescent glioma cells alter tumor microenvironment, such as increasing glioma stem cells, angiogenesis, and tumor-associated Ly6G + neutrophil cells via NFκB signaling-mediated activation of the senescence-associated secretory phenotype. Inhibiting NFκB signaling in irradiated glioma cells using the IκBα super-repressor prevents changes in the tumor microenvironment and glioma stem cells. tumor-associated Ly6G + cells promote the dedifferentiation of glioma cells into glioma stem cells through the NOS2-NO-ID4 regulatory axis. Depleting tumor-associated Ly6G + cells using Ly6G-neutralizing antibodies reduces glioma stem cells and prolongs survival in mice with recurrent gliomas after radiotherapy. In recurrent glioblastoma patients, neutrophil markers and tumor-associated neutrophils gene sets correlate with gene sets of NOS2-NO-ID4 regulatory axis and stem cell factors. Conclusions: Our results suggest the need to develop new radiation sensitizers targeting neutrophils driven by senescence-associated secretory phenotype and cancer cell dedifferentiation. Legal entity responsible for the study: The authors. Funding: National Research Foundation of Korea (NRF) [Grant numbers: 2015R1A5A1009024 and 2017R1E1A1A01074205], the School of Life Sciences and Biotechnology for BK21 Plus, Korea University and Institute of Animal Molecular Biotechnology, Korea University. Disclosure: All authors have declared no conflicts of interest.